2001
DOI: 10.1063/1.1408278
|View full text |Cite
|
Sign up to set email alerts
|

Modulating fluorescence of 8-quinolinolato compounds by functional groups: A theoretical study

Abstract: Substituent dependence of a fluorescence energy of the 8-quinolinolato anion (Q−) was systematically investigated with electronic structure calculations. Large red- and blueshifts of the fluorescence were predicted for Q− with the NO2 and CN groups, respectively. For bis(8-quinolinolato)berylium with the NO2 and CN groups, the emission energies were calculated to be 1.56 eV (795 nm) and 2.66 eV (466 nm), respectively, indicating that they are potential candidates as red- and blue-light-emitting compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 12 publications
0
18
1
Order By: Relevance
“…Experimental results revealed that the emission wavelength of Gaq 3 is longer than that of Alq 3 despite their similar molecular structure, and that emission occurs on the same ligand with different electron cloud structures. Although a previous study indicated that the emission properties of the ligand dominate the fluorescence of the complexes [22], this study showed that the central metal ion does influence the emission properties of these materials. Quantum chemistry calculations were used to examine the geometric and electronic structure of the lowest excited states of the two molecules to interpret the effect of charge transfer from the metal to the ligand on the luminescence characteristics of organic semiconductors chelated to metal ions.…”
contrasting
confidence: 73%
“…Experimental results revealed that the emission wavelength of Gaq 3 is longer than that of Alq 3 despite their similar molecular structure, and that emission occurs on the same ligand with different electron cloud structures. Although a previous study indicated that the emission properties of the ligand dominate the fluorescence of the complexes [22], this study showed that the central metal ion does influence the emission properties of these materials. Quantum chemistry calculations were used to examine the geometric and electronic structure of the lowest excited states of the two molecules to interpret the effect of charge transfer from the metal to the ligand on the luminescence characteristics of organic semiconductors chelated to metal ions.…”
contrasting
confidence: 73%
“…1 H, 13 C ATP (APT = attached proton test), and 19 F NMR spectra were recorded by using a Varian Unity 400 spectrometer with a working frequency of 400.0 MHz. Chemical shifts were referenced to the residual resonance signal of the deuterated solvent.…”
Section: Methodsmentioning
confidence: 99%
“…It is noteworthy that compounds 1 e and 1 f do not follow the trend in the aryl-A C H T U N G T R E N N U N G ethynyl series; this can be explained by considering that partial localization of the LUMO density on the nitro and pyridinium oxide moieties and alteration of the nature of the excited state take place. [13] Furthermore, the fluorescence quantum yields and lifetimes exhibited excellent Hammett correlations with the constants s p . [29,30] This shows that the electronic effects are projected through the conjugated spacers to the quinolinolate emitter, thus providing an effective tool not only for systematic tuning of the photophysical properties, but also Electrochemical studies-estimation of HOMO/LUMO levels: Solution electrochemistry methods are known to provide insight into electron-transfer reactions in the condensed phase.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In addition, -CN and -NO 2 have a large influence on the lowest unoccupied molecular orbital (LUMO) through p orbital interactions and result in the red shift of absorption wavelengths with respect to the electron-donating group [18][19][20]. In this paper, we use a serious of electronwithdrawing groups (-CF 3 , -CN, -NO 2 ) in the side chain of the OXD-X as meta-substitution, and settle F on the central phenyl ring as ortho-substitution.…”
mentioning
confidence: 99%